COMPLAINTS ON SLEEP BREATHING DISORDER AND CARDIOVASCULAR RISK FACTORS IN RUSSIAN REGIONS: DATA FROM ESSE-RF STUDY - M. V. Bochkarev; L. S. Korostovtseva; I. A. Filchenko; О. P. Rotar; Yu. V. Svirjaev; Yu. V. Zhernakova; S. А. Shalnova; А. О. Konradi; I. Е. Chazova; S. A. Boytsov; Е. V. Shlyakhto (Российский кардиологический журнал, 2018)
Aim. Evaluation of the prevalence of sleep breathing disorder (snoring, apnea) and its association with the risk factors of cardiovascular diseases, in the framework of the study of epidemiology of cardiovascular diseases risk factors in various regions of Russia (ESSE-RF).Material and methods. The object of the trial ESSE-RF were representative selections from non-organized male and female inhabitants, age 25 to 64 y. o., in 13 regions of Russia. From the module of sleep assessment, for breathing disorders the following questions were taken: “Do you snore at sleep?”, “Do you have interruptions of breathing during sleep?” with the variants yes, no, not known. Also the gender, age, systolic pressure were assessed, as obesity, physical activity level, smoking, alcohol consumption, systolic and diastolic pressure, complaints on sleepiness, laboratory parameters: lipid profile, fasting glucose, creatinine, glomerular filtration rate and uric acid.Results. Into analysis, 2 selection of participants were included, responded yes or no about snoring (n=17461) and sleep breathing interruptions (n=13264). The results show that the prevalence of complaints on snoring increased with smoking, alcohol overconsumption, male gender, age, body mass index, glycemia, low physical activity; and for apnea — male gender, alcohol, age and obesity. Sleepiness increases significantly with the complaints on snoring and apnea.Conclusion. Complaints on snoring are widely prevalent in general population with predomination among males. With the age, the prevalence increases of both snoring and apnea. Common risk factors of cardiovascular diseases in the presence of complaints on snoring and apnea, are male gender, obesity, age and alcohol overconsumption.